A genome-wide association study of high-sensitivity C-reactive protein in a large Korean population highlights its genetic relationship with cholesterol metabolism - Kwangyeon Oh; Minju Yuk; Soyoun Yang; Jiyeong Youn; Qian Dong; Zhaoming Wang; Nan Song (Scientific Reports)
Abstract High-sensitivity C-reactive protein (hsCRP) is a representative biomarker of systemic inflammation and is associated with numerous chronic diseases. To explore the biological pathways and functions underlying chronic inflammation, we conducted a genome-wide association study (GWAS) and several post-GWAS analyses of the hsCRP levels. This study was performed on data from 71,019 Koreans and is one of the largest East Asian studies. Overall, 69 independent single nucleotide polymorphisms (SNPs) were identified, including 13 novel variants. The implicated genes and pathways are primarily involved in cholesterol metabolism and the immune response. A phenome-wide association study was performed based on a polygenic risk score (PRS) constructed using 69 hsCRP-associated SNPs. Notably, the alleles associated with higher hsCRP levels appeared to be associated with lower low-density lipoprotein cholesterol levels (P = 1.69 × 10–33, β = -1.47) and higher γ -glutamyl transpeptidase (P = 8.30 × 10–8, β = 0.84). It suggests that increase in genetically determined hsCRP may contribute to a decrease in cholesterol level and a strong oxidative environment in the blood vessel. Thus, individuals with higher hsCRP-PRS may have a greater risk of cardiovascular diseases. Our findings suggest the genetic association between cholesterol and hsCRP, as well as the clinical importance of hsCRP-PRS for predicting the potential risk of cardiovascular diseases.